2019
DOI: 10.1007/s10905-019-09723-y
|View full text |Cite
|
Sign up to set email alerts
|

Do Female Red Flour Beetles Assess both Current and Future Competition during Oviposition?

Abstract: Female insects must assess multiple factors when laying eggs, including both abiotic and biotic conditions of the laying site. Competition may also play a crucial role in the oviposition decisions of females. Competition at oviposition sites may take two forms: current competition between adults for both food and access to sites for oviposition, and future competition between offspring that will hatch and develop at that site. Here, we test whether female red flour beetles (Tribolium castaneum) assess both cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…1939; Janus 1989). Thus, one way to increase offspring development rate under high resource competition is to decrease fecundity, and T. castaneum females may employ this strategy (Halliday et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1939; Janus 1989). Thus, one way to increase offspring development rate under high resource competition is to decrease fecundity, and T. castaneum females may employ this strategy (Halliday et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, fecundity and oviposition choice are inextricable; though most prior work on female context has focused on fecundity alone (Awmack & Leather 2002; Berger et al . 2008; Halliday et al . 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Oviposition is suppressed by conditioning of the medium and increased by egg cannibalism (Sonleitner and Gutherie 1991 ). Recent work has shown that females evaluate current and future competitive conditions when making oviposition decisions (Halliday et al 2019 ). Larval development is slowed by increasing larval and adult density (Park et al 1939 ; Janus 1989 ).…”
Section: Population Dynamicsmentioning
confidence: 99%
“…In the present work, we tested multiple novel hypotheses vis-à-vis analysing the relative impacts of diverse counter-strategies such as natal resource access, increased dispersal, and carcass scavenging to reduce the density-dependent female interference competition. We used T. castaneum since they are already an established model system to study female competition (Khan et al 2018;Halliday et al 2019). Wild populations of Tribolium beetles are also generalised feeders, show cannibalism (Via 1999) and can survive as natural predator and scavengers of other insects in a range of habitats such as nests of birds or eusocial insects and stored product environments (reviewed in Dawson 1976;Alabi et al 2008).…”
Section: Introductionmentioning
confidence: 99%